Relationship between Technological Frames and Technology Transfer - Aziz , Yahya; Safiah , Sidek; Aida Nasirah, Abdullah; Kalthom, Hussain; Rahman, Hashim; Hanipah, Hussin; Hazmilah, Hasan (Penerbit Universiti, UTeM, 2010)
This paper discusses a proposal to study the complex relationship of technological frames and the role it may plays in technology transfer. Using Communication Based Model, the study tries to seek answers for the following research questions. What is the relationship between similar technological frames and technology transfer among Subject Matter Expert (SME) and the line operators at an interpersonal communication level of analysis. Findings of this study may offer contributions for researcher as well as organizational development and communication specialists and manufacturing company managers.